Developing of Doing Proof for School Mathematics through Teaching and Learning - Rif’at, Mohamad; Sudiansyah, Sudiansyah; Peterianus, Septian (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
The word and the etymological sense are two hints about effective use of language, about exploration techniques, and about developing representation of information. For example, the length and width of a rectangle are not about position, but a measurement or a quantity concept. Based on the example, an area problem which given a picture and the measurements is not mathematics problem. That is a language trajectory of representations or a problem of the etymological sense. When asked to find the perimeter of rectangle, but the two quantities are whole numbers and neither is divisible by 6, then, that is mathematics trajectory. However, if the area known, say 36 squares of a measure unit, then problem of getting the perimeter is to test or to check. That is also a kind of the etymological sense of meaning